18 Prediction of Immune-Related Adverse Events (irAEs) with Hematologic Markers in Patients Receiving First-Line Immune Checkpoint Inhibitor (ICI)-Based Therapy in Metastatic Renal Cell Carcinoma (mRCC) - Rahul Winayak; Xiaochen Li; Vitor Abreu de Góes; Ali Moradi; Salvador Jaime Casas; Koral Shah; Nicholas Salgia; Benjamin Mercier; Michelle Li; Jadon Fann; George Zhang; Ruchi Agarwal; et al. (The Oncologist, 2026)
Abstract Background First-line therapies with combinations of ICI-ICI and ICI-tyrosine kinase inhibitor (TKI) are commonplace in mRCC. Frequency of irAEs in patients receiving first-line ICI-based therapies is high, with grade ≥ 2 (G ≥ 2) typically warranting active management. Although prognostication based on irAEs has been demonstrated, prediction of irAE occurrence in mRCC remains a challenge. We investigated the role of baseline hematologic markers to predict G ≥ 2 irAE occurrence with first-line ICI-based therapies in mRCC. Methods We used the City of Hope database (encompassing 5 centers across 4 states) to retrospectively identify mRCC patients treated with first-line ICI-based therapies from September 2015 to September 2025. Baseline patient demographics, including age, gender, Karnofsky Performance Status (KPS), pre-existing autoimmune condition, IMDC risk group and first-line ICI-based regimen were collected. We stratified baseline hematologic markers, including neutrophil-to-lymphocyte ratio (NLR), neutrophil-to-eosinophil ratio (NER), platelet-to-lymphocyte ratio (PLR), systemic inflammatory index (SII) and absolute eosinophil count (AEC), into high and low levels using recursive partitioning, and evaluated their association with occurrence of first-line ICI-related G ≥ 2 irAEs. Results A total of 198 patients with mRCC were treated with first-line ICI-based therapy, of which 5 were excluded due to insufficient data. Of the 193 evaluable patients, the mean age was 61, 131 patients (67.9%) were male, 100 patients (51.8%) received ICI-ICI and 93 patients (48.2%) received ICI-TKI. G ≥ 2 irAEs were observed in 55 patients (28.5%), requiring systemic steroid use in 32 patients (16.6%) and treatment discontinuation in 30 patients (15.5%). The most common G ≥ 2 irAE was ALT/AST elevations, seen in 16 patients (8.3%). Of the baseline hematologic markers studied, increased PLR and SII were most strongly associated with occurrence of G ≥ 2 irAEs (P < 0.005 for each). Conclusions Our results point to a novel potential role of PLR and SII as predictive biomarkers of G ≥ 2 irAEs, with ICI-based therapies in mRCC, meriting further validation in prospective studies.